The Constitutional Processes in Kenya and Zimbabwe: A Comparative Perspective (The Strategic Review for Southern Africa, 2020)
In recent years, Kenya and Zimbabwe have been described in comparative terms. The similarities between the two countries include a shared colonial legacy, common experiences in the areas of power sharing, equitable distribution of resources, economic asymmetries, regional disparities, corruption and electoral reforms. The Independence Constitutions of the two countries were negotiated at Lancaster House in London, Britain, and are both referred to as Lancaster House Constitutions. Both countries have grappled with the challenge of creating widely accepted constitutions. Using a comparative case study approach, the article discusses the processes of constitution-making in the two countries. Although the article recognises the importance of content, it largely focuses on the processes leading to the creation of the 2010 and 2013 Constitutions of Kenya and Zimbabwe, respectively.